Nitrogen doped carbide derived carbon aerogels by chlorine etching of a SiCN aerogel - Zera, E.; Nickel, W.; Hao, G. P.; Vanzetti, L.; Kaskel, Stefan; Soraru, G. D. (Journal of Materials Chemistry A, 2016)
Silicon was selectively removed from a silicon carbonitride (SiCN) aerogel by hot chlorine gas treatment, leading to a N-doped carbon aerogel (N-CDC aerogel). The combined effects of pyrolysis and etching temperature were studied with regard to the change in the composition of the material after etching as well as the microstructure of the produced hierarchically porous material. Upon removal of Si from amorphous SiCN, carbon and nitrogen, which are not bonded together in the starting material, react, creating new C-N bonds. The removal of silicon also gives rise to a high amount of micropores and hence a high specific surface area, which can be beneficial for the functionality of the carbonaceous material produced. The mesoporous structure of the aerogel allows us to complete the etching at low temperature, which was found to be a crucial parameter to maintain a high amount of nitrogen in the material. The combination of a high amount of micropores and the mesopore transport system is beneficial for adsorption processes due to the combination of a high amount of adsorption sites and effective transport properties of the material. The N-CDC aerogels were characterized by nitrogen physisorption, X-ray photoelectron spectroscopy (XPS), thermogravimetry (TG/DTA), and infrared spectroscopy (DRIFT) and they were evaluated as CO2 absorbers and as electrodes for electric double-layer capacitors (EDLCs).
CRIS-Team Scopus Importer:2023-03-20